Combined sequential hypothermic oxygenated and normothermic machine perfusion for liver transplant from an expanded criteria donor: first clinical application in Russia - S. V. Gautier; N. V. Grudinin; A. R. Monakhov; M. A. Boldyrev; V. K. Bogdanov; D. M. Bondarenko; S. I. Zubenko; N. P. Mozheiko; M. G. Minina; O. M. Tsirulnikova (Вестник трансплантологии и искусственных органов)
Objective: to analyze a clinical case series and evaluate the safety and efficacy of a sequential machine perfusion protocol combining dual hypothermic oxygenated perfusion (D-HOPE) and normothermic machine perfusion (NMP) for conditioning and viability assessment of liver grafts retrieved from expanded criteria donors (ECD) in routine clinical practice.Materials and methods. Between November and December 2024, two sessions of combined D-HOPE followed by NMP were conducted at Shumakov National Medical Research Center of Transplantology and Artificial Organs («Shumakov Research Center») using liver allografts obtained from ECD after brain death. Following an initial period of static cold storage (SCS), machine perfusion was initiated using a circulatory assist device. A histidine-tryptophan-ketoglutarate (HTK)-based perfusate was used during the DHOPE phase, while a red blood cell (RBC) suspension was used during the NMP stage. Throughout perfusion, temperature and hemodynamic parameters were continuously monitored and maintained. Laboratory parameters were assessed at designated intervals, in accordance with the institutional protocol developed at Shumakov Research Center.Results. Allograft #1 was deemed non-viable due to elevated lactate levels after 3 hours of perfusion and lack of glucose metabolism. The preservation times were as follows: SCS – 424 minutes, D-HOPE – 120 minutes, NMP – 300 minutes, totaling 844 minutes. Allograft #2 met the viability criteria and was successfully transplanted. Preservation times were: SCS – 260 minutes, D-HOPE – 124 minutes, NMP – 480 minutes, with a total preservation time of 884 minutes. Post-transplant peak levels of AST, ALT, and total bilirubin in the recipient were 922.5 U/L, 613 U/L, and 63.3 μmol/L, respectively. The only postoperative complication was acute kidney injury, managed with two sessions of hemodialysis. The patient was discharged after 14 days of hospitalization without need for readmission. At the time of writing, the patient is alive and complication-free, with a follow-up period of 3 months.Conclusions. Combined machine perfusion of liver grafts appears to be a safe and effective strategy to mitigate ischemia-reperfusion and preservation-related injury in liver transplantation. It also facilitates viability assessment of marginal liver grafts, reduces potential recipient complications, and expands the donor pool through the use of allografts from ECD.